Cultural Representation and User Perceptions in Indonesian English Textbooks: A Mixed-Method Analysis - Suadi Suadi; Muhammad Ari Saputra; Ayu Meita Puteri Siregar; Zelly Putriani (J-Lalite: Journal of English Studies, 2026)
This study is urgent because English textbooks in Indonesia play a central role in shaping readers’ linguistic development and intercultural awareness, yet existing materials are still insufficiently evaluated in terms of how culture is represented and perceived. A qualitative approach with a mixed-method analysis was employed. First method was conducted for analysing cultural content on three English educational textbooks: When English Rings a Bell for Grades VII and VIII, and Think Globally, Act Locally for Grade IX based on the frameworks of Cortazzi and Jin (1999), Silvia (2014), Moran (2001), and Yuen (2011)’s cultural model. Second method was by applying thematic analysis on result of a semi-structure interview by involving 18 respondents who are actively engaged in an academic setting from 6 different educational institutions in Indonesia to gain their cultural views on English textbooks. The findings of cultural types (the origin of culture) showed 156 appearances in total, comprising 60 (38.5%) appearances of source culture, 6 (3.8%) of target culture, 7 (4.5%) of international target culture, and 83 (53.2%) of culture-free content. Moreover, cultural elements (the forms of culture) showed 156 appearances. Of these, 107 (68.5%) were categorized as product, 43 (27.5%) as practice, 2 (1.3%) as perspective, and 4 (2.5%) as person. Thematic analysis on the data of semi-structured interview shows cultural contents were inseparably crucial integrated in English educational textbooks for users’ better understanding of English mastery and inclusive culture. Ultimately, this study recommends English educational textbooks should emphasize the integration of culturally inclusive materials to enhance readers’ English skill and promote the English non-native speakers’ engagement through culturally relevant instruction.